Cochrane Database of Systematic Reviews 2013
DOI: 10.1002/14651858.cd009593.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Xpert® MTB/RIF assay for pulmonary tuberculosis and rifampicin resistance in adults

Abstract: Background Accurate and rapid detection of tuberculosis (TB) and drug resistance are critical for improving patient care and decreasing the spread of TB. Xpert® MTB/RIF assay (Xpert) is a rapid, automated test that can detect both TB and rifampicin resistance, within two hours after starting the test, with minimal hands-on technical time, but is more expensive than conventional sputum microscopy. Objectives To assess the diagnostic accuracy of Xpert for pulmonary TB (TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
260
5
12

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 322 publications
(304 citation statements)
references
References 74 publications
12
260
5
12
Order By: Relevance
“…The data presented here on 452 samples show that the Xpert assay correctly identified RMP susceptibility in 451 of 452 patients. This is excellent performance, considering that the pooled sensitivity and specificity of the Xpert assay for RMP resistance detection in pulmonary samples have been reported as 95% and 98%, respectively (17). The data also support the high (99%) negative predictive value of the Xpert assay for RMP resistance detection, as suggested by the WHO data for settings with a low prevalence of RMP resistance (10).…”
supporting
confidence: 66%
“…The data presented here on 452 samples show that the Xpert assay correctly identified RMP susceptibility in 451 of 452 patients. This is excellent performance, considering that the pooled sensitivity and specificity of the Xpert assay for RMP resistance detection in pulmonary samples have been reported as 95% and 98%, respectively (17). The data also support the high (99%) negative predictive value of the Xpert assay for RMP resistance detection, as suggested by the WHO data for settings with a low prevalence of RMP resistance (10).…”
supporting
confidence: 66%
“…We have shown that the sample extraction process workflow is capable of processing the most purulent portion of sputum (the "core"), and this tended to generate the best PCR amplification profiles in comparison to samples taken from the more fluid peripheral parts of the sputum samples. However, other factors, such as the condition of the specimen (fresh versus frozen) or the specimen preparation (decontamination), were found to alter the performance of the Genedrive system to some degree (data not shown), as has been reported for the GeneXpert system (20). An advantage of the sample processing workflow in the Genedrive instructions for use is the ability to use a small sample volume.…”
Section: Discussionmentioning
confidence: 78%
“…Since the incidence of genotypic false-positive RIF resistance depends on the prevalence of RIF resistance in a given population (34,35), the unresolved clinical questions are how to accurately correlate genotype with drug susceptibility phenotypes while fulfilling the medical community's requirements for and desired attributes of a rapid molecular TB test (3,36,37). The answer to these questions is especially important when the prevalence of drug resistance in a population is low (Ͻ5%), when RIF resistance alone is used as a surrogate marker for MDR M. tuberculosis, or when the availability of second-line drugs is limited.…”
Section: Discussionmentioning
confidence: 99%